Chapter 12. Calibration of Chemical Applicators Used in Vegetables - Richard K. Sprenkel (EDIS)
Calibration is the process of determining the amount of material applied per acre. Equipment for applying both liquid and dry material must be accurately calibrated for the pesticide to work properly and to avoid damaging or killing the crop if, the case in the case of herbicides, too much is applied. Also, since the label on a container of pesticide is considered to be a legal document, calibration of equipment ensures the product is being applied as specified on the label and that environmental contamination will be minimized. Some methods for calibration sprayers and d material spreaders are described in this document. This document is AE261, one of a series of the Horticultural Sciences Department, UF/IFAS Extension. Original publication date June 1995. Revised November 2006.